Improving speech intelligibility in noise and spatial perception: the critical role of hearing aid microphone position - Kara, Eyyup; Özal, Nurşah; Deniz, Burcu; Çögen, Talha; Deniz, Rışvan; Aydın, Kübra; Caba, Cenk; Yılmaz, Begüm Bahar (Frontiers in Neuroscience, 2024)
IntroductionHearing aid (HA) manufacturers have introduced behind-the-ear (BTE) models where the microphone is positioned in the ear canal, which could impact auditory performance by distorting the pinna’s acoustic cues. This study aimed to compare two different BTE HAs with varying microphone positions: the receiver in the ear (RITE) and the transducer in the ear (TIE).MethodsThe study involved 10 participants who had never used HAs before. They used both RITE and TIE HAs bilaterally for 3 weeks. Auditory performance was assessed through free field hearing assessments (hearing thresholds, speech recognition threshold, and speech discrimination score), the Turkish Matrix Sentence Test (TURMatrix), a sound localization test, and the Satisfaction with Amplification in Daily Living (SADL) questionnaire.ResultsThere was no significant difference between TIE and RITE in the free field hearing assessments. However, TIE outperformed RITE in non-adaptive TURMatrix scores in quiet, adaptive TURMatrix scores in noise, and sound localization accuracy at various angles. SADL sub-scores (Positive Effect, Service and Cost, and Personal Image) and overall satisfaction scores were significantly better for TIE.DiscussionThe microphone position in HAs can influence auditory performance. This study demonstrated that TIE provided better speech intelligibility, localization accuracy, and user satisfaction compared to RITE.